Incentives to diffuse advanced abatement technology under environmental liability law - Endres, Alfred; Friehe, Tim (My University, 2011)
Polluting firms with advanced abatement technology at their disposal have incentives or disincentives to share this technology with other polluting firms. The ‘direction’ and extent of those incentives depends on the liability rule applicable and the way technical change impacts marginal abatement costs. We establish that incentives for diffusion are socially optimal under strict liability and socially suboptimal under negligence if technical change lowers marginal abatement costs for all levels of abatement. Negligence may, however, induce better diffusion incentives than strict liability if technical change decreases (increases) marginal abatement costs for low (high) levels of abatement.
Keywords: Environmental liability law; Emission abatement technology; Diffusion; 330